A Consumers Demand Model with "Energy Flows", Stocks and "Energy Services" - Kurt Kratena; Michael Wüger (Austrian Institute of Economic Research (WIFO), 2004)
This paper sets up a model of private consumption for selected EU countries with special emphasis on the consumption categories heating and transport. Sustainable consumption patterns require a "decoupling" of energy or materials use from satisfaction of consumers' needs and demands. Starting point for the analysis is the observation that the ultimate goal of consumption is utility maximization and that utility is determined by the consumption of goods as well as the level of "services", produced with inputs of other consumption goods. These other goods are energy flows and capital services. Exogenous key variables that can be modified in order to calculate different scenarios are: (i) prices of energy and non-energy goods (ii) the exogenous capital stock (infrastructure) or user costs of capital.
Keywords: D11; D13; Q53; 330; Privater Konsum; Energiekonsum; Kapitalkosten; Haushaltsproduktion; Schätzung; EU-Staaten